The Impact of Green Technology and Industrialization on Environmental Performance in Oil-Producing Countries: A Dynamic ARDL Approach (Innovations in Environmental Economics, 2025)
This study investigates the dynamic effects of industrialization and green technology on environmental performance in 13 oil-producing countries in the Middle East and North Africa (MENA) region over the period 2005–2025. Using panel data and the Autoregressive Distributed Lag (ARDL) approach, both short-run and long-run relationships among the variables are examined. The empirical findings confirm the existence of a long-run equilibrium relationship between the study variables. The results indicate that industrialization exerts a strong, long-term detrimental effect on environmental performance, whereas green technology has a positive but relatively weak effect. Similar patterns are observed in the short run: industrialization negatively affects environmental performance, while green technology positively affects it. In contrast, trade competitiveness, human development, and urbanization do not exhibit statistically significant effects. The error-correction term suggests that approximately 10% of short-run disequilibrium is corrected in each period, indicating a relatively slow adjustment toward long-run equilibrium. The findings imply that industrialization in oil-producing economies remains predominantly pollution-intensive due to the abundance and low cost of fossil fuels. At the same time, the limited penetration of green technologies has constrained their mitigating impact on environmental degradation. Accordingly, the study recommends adopting green industrialization policies, accelerating the transition to renewable energy, attracting environmentally friendly foreign direct investment, strengthening human capital, reforming fossil fuel subsidy systems, and enhancing regional environmental cooperation.